The Social Transformation of Japanese Society Depict on the Film Ososhiki - Zida Wahyuddin; Lilawati Kurnia (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
This paper examines and observe the concept of Nihonjinron and reveals the social transformation of Japanese society. Through the Japanese Society by Nakane Chie (1970) and The Anatomy of Dependence by Takeo Doi (1973), and the film Osōshiki (1984), it will reveal the social transformation of Japanese society in a historical context. In this context, Japan is one example of a community of people who experience social transformation. The method to be used is a qualitative for studying cinema with a sociological and historical approach. The analysis will focus on the change in the tradition of the funeral ceremony which is obtained from the narrative and cinematographic aspects of the film and then compared with the concepts in Nakane Chie and Takeo Doi’s books. The results of the analysis will be read with sociological concepts, especially about social transformation in Japan. The result is a contribution of knowledge related to social transformation and a criticism of established traditional values. In addition, this paper contributes to how Japanese films have a strategy in recording as well as providing references regarding social criticism due to progress and modernization in the context of the tradition of death ceremonies in film. Keywords: Nihonjinron, Social Transformation, Sociology of Film, Funeral Ceremony